2003
DOI: 10.1186/1471-5945-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-reported eczema in relation to living environment, socio-economic status and respiratory symptoms assessed in a questionnaire study

Abstract: Background: Potential links between eczema and obstructive pulmonary diseases have been postulated. Previously we have reported the prevalence of upper and lower respiratory diseases and the relation to environmental and socio-economic factors in a randomly selected adult population in southern Sweden using a postal questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
44
5
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 22 publications
12
44
5
1
Order By: Relevance
“…The developing country like Nigeria needs enforcement of extant laws that forbids smoking within enclosures at home and in the public places. Although smoky cooking; using kerosene stove and firewood were not significantly associated with allergic disorders in the present study after multivariate analysis, Montnemery et al, and others [32,33] found living close to heavy traffic, which is a heavy source carbon monoxide pollution, hereditary history of eczema and selfreported rhinitis as important risk factors for allergic conditions. There is increasing need for the improvement of socio economic conditions of dwellers in the sub-Sahara Africa and emission control of air pollutant.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The developing country like Nigeria needs enforcement of extant laws that forbids smoking within enclosures at home and in the public places. Although smoky cooking; using kerosene stove and firewood were not significantly associated with allergic disorders in the present study after multivariate analysis, Montnemery et al, and others [32,33] found living close to heavy traffic, which is a heavy source carbon monoxide pollution, hereditary history of eczema and selfreported rhinitis as important risk factors for allergic conditions. There is increasing need for the improvement of socio economic conditions of dwellers in the sub-Sahara Africa and emission control of air pollutant.…”
Section: Discussioncontrasting
confidence: 68%
“…Prevalence of eczema is inversely related to age [34,35]. Montnemery et al, found a higher prevalence of 8.2 to 17.1% among actively working adults [32], highest prevalence was recorded among non-manual workers. Although available data are very limited, the clinical fluctuation of eczema like asthma in pregnancy is complex [8,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 98%
“…Trucks frequently passing home areas was identified as one of potential environmental factors associated with rash, eczema, and atopic dermatitis. This is in agreement with the finding of Montnemery et al (2003) who investigated that living close to heavy traffic was identified as an environmental factor associated with eczema among adults in Sweden. Scha¨fer and Ring (1997) investigated the influence of air pollution on the prevalence of atopic eczema among German schoolchildren and reported a higher prevalence of eczema among children living near roads with heavy traffic.…”
Section: Discussionsupporting
confidence: 93%
“…Atopic dermatitis (AD) is a chronic inflammatory disease with the lifetime prevalence of 8∼17% in adults under 60 years old and it has a number of subtypes 1 . Intrinsic AD (IAD) is differentiated from the much more common extrinsic type (EAD) by a total serum immunoglobulin E (IgE) level that is within the normal range, by the lack of specific IgE positivities and by the fact that no immediate skin reaction to environmental allergens or respiratory involvement can be observed [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%